The Analysis of the Stanislavsky’s System Schema (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article presents an overview of Konstantin Stanislavsky's system schema, the only one available in Portuguese so far. The object of investigation is a rare illustration found in Stanislavsky’s 1935 manuscripts, a schematic and poetic drawing that may synthesize the complex artistic and pedagogical thoughts of this theatre director. Based on a literature review, this work discusses all the fifteen components presented in the schema, considering their arrangement in the drawing and their interconnections. In addition, some specific concepts and terms of Stanislavsky's system are approached regarding its interpretative polemics. The resulting analysis may support future studies about the actor's art fundamentals concerning Stanislavsky's propositions.
Keywords: Stanislavsky’s system; acting; Stanislavsky’s system schema; theatre; actor